54 EXPLORING FEATURES AND OUTLOOK OF WOMEN DISCHARGED AFTER AN ACUTE CORONARY SYNDROME MANAGED INVASIVELY: INSIGHTS FROM THE 23, 072 PATIENTS PRAISE MULTICENTER REGISTRY. (15th December 2022) - Spadafora, Luigi; Zoccai, Giuseppe Biondi; Bernardi, Marco
Abstract: Background: Acute coronary syndromes (ACS) are a common cause of morbidity and mortality, irrespective of sex. While several studies have focused on ACS at admission or long-after the acute event, limited if any research is available on sex-based comparison of patients discharged after ACS. We aimed at appraising the outlook of women discharged after ACS, exploiting a large multinational registry. Methods: Details on women enrolled in the PRAISE multicenter registry, a large database spanning 23, 702 patients included between 2003 and 2019, were systematically collected. We focused on patient and procedural features, medications at discharge, and 1-year outcomes. The primary endpoint was the composite of death, myocardial infarction, or major bleeding after discharge. Secondary outcomes were the individual components of the primary endpoint. Results: Characteristics of 17, 804 men and 5, 466 women discharged after ACS were collected. Several baseline differences were found, including risk factors and history of prior revascularization (all p<0.05). At discharge, men underwent radial access more frequently, and received also more commonly beta-blockers, renin-angiotensin system inhibitors, and statins (all p<0.05). Focusing on antithrombotic therapy, men received more frequently prasugrel, whereas women receive more commonly clopidogrel (all p<0.05). At 2-year follow-up incidence of death, reinfarction, major bleeding, non-fatal major bleeding were significantly higher in women (all p≤0.01). All such differences were however due to residual confounding and did not hold true at multivariable analysis, with the exception of major bleeding, which appeared surprisingly lower in females at adjusted analysis (odds ratio=0.70 [95% confidence interval: 0.52-0.94], p=0.017). Conclusions: Women are treated less aggressively with apparently worst outcomes 2 years after discharge for ACS managed invasively. On the basis of these findings, we should change our approach and adopt a more aggressive management of women with ACS. Figure 1. Sex-based comparison of clinical outcomes 2 years after discharge for an invasively managed acute coronary syndrome (ACS) (all p<0.05).